Incentive Early Retirement Programs for Faculty : Innovative Responses to a Changing Environment - Chronister, Jay L.; Kepple, Thomas R., Jr.; Association for the Study of Higher Education; ERIC Clearinghouse on Higher Education ([Washington : Distributed by ERIC Clearinghouse, 1987)
The literature on incentive early retirement for faculty members is reviewed, including the findings of studies that have assessed the effectiveness of such programs. In addition to describing different types of programs and the incentives offered, attention is directed to legal issues, costs and benefits, assessing whether a program is feasible, and evaluating program effectiveness. Environmental factors that create the milieu in which early retirement programs have developed are briefly reviewed, including increased costs of faculty compensation, shifts in students' course preferences, and faculty morale. Attention is also directed to different types of programs and the purposes for which they have been established. Strategies and factors to be considered in deciding upon the development of programs are presented, using material from case studies. The experiences of selected institutions that have implemented early retirement programs and the reactions of faculty to such programs are also discussed. Recommendations for institutions considering the establishment or revision of incentive early retirement programs are offered. Definitions, key concepts, and terminology are included, along with a generic cost analysis formula. (SW)
Availability: Association for the Study of Higher Education, Publications Department, One Dupont Circle, Suite 630, Washington, DC 20036-1183 ($10.00, nonmembers; $7.50, members).
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: 400-86-0017.
Educational level discussed: Higher Education.
Microfiche.
Keywords: College Faculty